Investigation of the determinants of alcohol use among women in Oshikoto region, Namibia - Rebekka N. Netope; Emma M. Nghitanwa; Tuwilika Endjala (Journal of Public Health in Africa, 2023)
Background: Alcohol abuse is one of the world’s main public health issues. Alcohol use is growing among African women, and it has become an underlying factor in women’s health risk profiles.